MEDICAL STUDENTS' PERCEPTION OF CULTURAL COMPETENCE - Amin, Siti Azzahra Aulia; Octavira P, Tissa; Meidianawaty, Vivi (Universitas Gadjah Mada, 2025)
Background: Nowadays, medical education has begun to incorporate cultural competence into the curriculum to better prepare students for the challenges of health care, particulalrly in this era of globalization. Yet, students' perceptions of the importance of cultural competence still need to be evaluated.Methods: The study was a cross-sectional design with descriptive analysis. The data were collected using the Clinical Cultural Competency Questionnaire (CCCQ), which has been adapted and translated to assess knowledge, skills, comfort level, and attitude. The sample size was determined using consecutive sampling methods at various academic stages and clinical rotations. Results: Out of a total of 146 respondents, the mean results of cultural competence were found to differ among medical students by year of study, age, and number of co-assistant stations completed. Clinical rotation students achieved higher scores in the knowledge, skills, and comfort level domains compared to academic stage students. The mean scores in the knowledge, skills, and comfort level areas increased with age.Conclusion: Medical experiences in healthcare facilities and interactions with patients from diverse cultural backgrounds can influence cultural competence.